Commodity Zoning and Identification of Agricultural Practices Using an Agroecological Approach in Selur Village - Hutanti, Krisma (Indonesian Journal Publisher, 2025)
Selur Village is an agrarian village where most residents rely on the agricultural sector as their primary source of livelihood. However, this sector faces challenges such as limited irrigation access, suboptimal land management, and the impacts of climate change. Agroecology offers an integrative solution combining ecological, social, and cultural aspects to enhance agricultural sustainability. This study aims to delineate superior commodity zoning through agroecological maps tailored to the biophysical potential of the area and to understand local farming practices based on agroecological principles. The research employs a mixed-method approach, with primary data obtained through interviews with 18 farmers, analyzed using Deductive Qualitative Analysis (DQA) to describe current farming practices, which were then interpreted about agroecological principles. Secondary data, including slope, elevation, air temperature, rainfall, and soil type, were spatially analyzed using QGIS to produce agroecological zone maps. Land suitability assessment was conducted using the matching method, aligning land characteristics with crop growth requirements. The results indicate that the majority of land in Selur village is suitable for perennial crops and forestry. Key commodities such as rice, maize, turmeric, and horticultural crops exhibit high compatibility with land conditions. The findings emphasize the application of agroecological principles, including crop diversification, soil conservation, and resource recycling, but highlight the need for further interventions. The study concludes by recommending strategies such as sustainable intensification, land rehabilitation, and enhanced market access to optimize agricultural productivity and resilience in Selur Village.